2022
DOI: 10.1155/2022/8955660
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Neuroprotective Effect of a Single High-Dose Vitamin D3 in Patients with Moderate Ischemic Stroke

Abstract: Introduction. Vitamin D insufficiency is highly prevalent and is a negative predictor for survival in ischemic stroke patients. We evaluated the effect of a high dose of vitamin D3 on the Neuron-Specific Enolase (NSE) level, National Institute of Health Stroke Scale (NIHSS), and Barthel Index (BI) scoring system in moderate ischemic stroke patients. Methods. This prospective, double-blind, randomized clinical trial (RCT) study was conducted from April 2020 to March 2021. Patients with moderate ischemic stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…• High-dose vitamin D offered neuroprotective effects in patients with moderate ischemic stroke (Hesami et al, 2022). Similar action might be expected in patients with TBI.…”
Section: Clinical Investigation Of Novel Therapeutic Approachesmentioning
confidence: 68%
“…• High-dose vitamin D offered neuroprotective effects in patients with moderate ischemic stroke (Hesami et al, 2022). Similar action might be expected in patients with TBI.…”
Section: Clinical Investigation Of Novel Therapeutic Approachesmentioning
confidence: 68%
“…A total of 43 articles underwent full text review of which 33 studies were subsequently excluded (Figure 1 and Appendix B for list of excluded studies at full text stage). Ten studies were included in this systematic review, including eight randomized controlled trials 7,[18][19][20][21][22][23][24] and two non-randomized studies of intervention, 3,25 examining a total of 691 patients (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of vitamin D supplementation on activities of daily living was examined in four randomized controlled trials 19 , 21 , 22 : three 19 , 21 , 24 used the Barthel Index and one 22 used the Functional Independence Measure. Sari et al 21 and Hesami et al 24 both assessed the Barthel Index and found a significant improvement in the vitamin D supplementation group compared to placebo and usual care, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is evident that a single dose of 600000 IU of vitamin D 3 exerts neuronal protection by preventing reactive oxygen species damage and vasodilatation in moderate ischemia. The synergistic effect of vitamin A with vitamin D reduces serum IL-1β levels, resulting in a better outcome for ischemic stroke patients [ [3] , [4] , [5] , [6] ].…”
mentioning
confidence: 99%